Analysis of Dominant Factors in the Supply Chain Man-agement Process that Affect Consumer Loyalty in Student Cooperatives - Luthfia Rizky Ramadhansy; Bambang Darmawan; Dwi Novi Wulansari (Lembaga Pengembangan Kinerja Dosen, 2025)
Supply Chain Management (SCM) plays a strategic role in improving competitiveness and consumer loyalty. This study aims to analyze the SCM factors that influence consumer loyalty to the BS UPI Student Cooperative (Kopma). The approach used is quantitative with a survey method, involving 40 respondents who are students of the University of Education Indonesia who have made purchases at Kopma in the past three months. Data was collected through questionnaires and analyzed using confirmatory factor analysis. The results of the study indicate that product variety, price, timeliness, facilities, availability, and product quality are important factors influencing consumer loyalty. From the analysis, it was found that product variety is the dominant factor most influencing consumer loyalty. The decline in Kopma's sales over the past two months underscores the need to enhance SCM strategies to maintain and improve consumer loyalty. These findings are expected to serve as a reference for Kopma managers in formulating more effective SCM strategies to address competitive challenges and meet consumer expectations optimally.